Groundwater resource assessment in Astaneh-Kouchesfahan Plain, Iran - Saatsaz, Masoud (2011)
Astaneh-Kouchesfahan Plain is one of the focus points in terms of regional development in north of Iran. The socio-economic resources of the plain are enormous and play a particularly important role in supporting the rural population of the area. Partial use of groundwater potential, increase in irrigation demand and groundwater contamination have caused the cultivable lands not to be fully exploited and because of secondary salinity and erosion, surface soils gradually are being converted to idle lands. This problem has brought some difficulties for economical development of the area that has led to decrease of family income, unemployment and finally immigration of rural people. Most of these difficulties are due to mismanagement of water resources caused by lack of reliable data. Hence, for overcoming these difficulties, a detailed regional quantitative and qualitative assessment of groundwater resources has been proposed and the results have been analyzed based on standard methods. The base investigations were carried out to develop hydrogeological and hydrochemical frameworks of the groundwater system. Based on available data, average annual water balance has been evaluated for the whole region. Groundwater balance study indicates that despite of water deficiency for domestic and agricultural usages, discharge from groundwater is less than recharge to the region. The results show that total recharge into the system is of the order of 342.89 million m3 (MCM), whereas the total discharge is of the order of 332.89 MCM, leaving a surplus balance of +9.99 MCM. From the hydrochemical point of view, the groundwater sources in the Astaneh-Kouchesfahan Plain have been evaluated for their chemical composition and suitability for drinking and irrigation uses. Comparison of geochemical results with World Health Organization and United States Environmental Protection Agency standards show that most groundwater samples except few are permissible for drinking purposes and based on the Wilcox diagram, nearly all of the groundwater samples are fit for irrigation use in almost all soil types. The groundwater in the region was classified as hard, fresh to brackish, medium to high saline and slightly alkaline in nature. The Piper plot illustrates that most of the groundwater samples analyzed during the pre-monsoon and post-monsoon fall in the field of Ca-HCO3. In order to achieve a better understanding of the nature of the factors influencing ground water composition, the correlation studies and R-mode factor analysis were carried out on the various groundwater parameters and the factor scores were transferred to areal maps. The results of factor analysis show that factor 1 of the pre-monsoon and factor 2 of the post-monsoon have high loading in the ions Na+ and Cl-, reflecting that these ions are mainly derived from dissolution of secondary salts precipitated in the pore spaces and anthropogenic sources such as agricultural activities and influx of municipal effluents. After hydrochemical investigations, the groundwater vulnerability to pollution was evaluated using GIS DRASTIC model and the obtained results showed the areas with low, moderate, high and very high groundwater vulnerability potential cover around 12, 52, 28 and 8% of study area, respectively. The high and very high vulnerable zones mainly located in middle parts of the plain and hence, groundwater resources beneath such areas need to be monitored continuously so that protective measures can be established. In this study, a 2-Dimentional groundwater flow model was also developed and calibrated to simulate and predict hydraulic heads under steady-state and transient conditions; to optimize hydrogeological coefficients values of aquifer; as a prerequisite, to develop a contamination-transport model and finally, to validate GIS DRASTIC model using model scenario testing. The results of the transient calibration indicate that the horizontal hydraulic conductivity values ranges from 1 to 23 m/day; and the specific yield of the aquifer ranges between 0.03 and 0.25. After model verification and assurance the reliability of the model results, the model prediction has been done for the period from October 2009 to October 2012 and it has been predicted that according to present recharge and discharge conditions, the average weighted groundwater levels rise about 0.34 m. At the same period, the predictive results of solute transport model show that according to present flux conditions, groundwater salinities increased by approximately 2% over the period and the average weighted chloride concentration increases from 136.36 to 138.89 mg/L. However, if current conditions prevail, it is expected that the groundwater consumers of the aquifer will be facing a worse situation than the present condition. Key Words: Aquifer Management, Aquifer Vulnerability, Astaneh-Kouchesfahan Plain, DRASTIC, GIS, Groundwater Balance, Groundwater Pollution, Groundwater Simulation, Hydrochemistry, Hydrogeology, Iran, MT3D Model, , Numerical Modeling, PMWIN Model, Recharge, Water Budget, Water Quality.